Menerapkan Pendekatan Penelitian dan Pengembangan dalam Pembuatan Konten Media : Sebuah Studi Kasus Media Indonesia - Brenda Syahirah; Suparman Suparman (Badan Penerbit STIEPARI Press, 2025)
The development of information and communication technology has encouraged mass media to transform significantly, both in terms of format and content presentation strategy. This study aims to describe the strategic role of Media Indonesia's Research and Development Department (R&D) in supporting data-based media content research and development activities. Using a descriptive qualitative approach, this study was conducted through direct observation, active participation, in-depth interviews, and literature study in Media Indonesia's R&D work environment. The results showed that R&D acts as a research and innovation center that applies a R&D approach based on the Borg and Gall model. Research and Development carries out the stages of initial research, content development, publication testing, and revision based on audience feedback to ensure the quality and relevance of the information presented. The findings confirm that R&D is an important pillar in a media ecosystem that is adaptive, innovative and responsible for the dynamics of public information needs in the digital era.